Impacto genotóxico de poluentes químicos presentes na água e sedimento do Rio Japaratuba (Sergipe) - Pantaleao, Silmara de Moraes (2006)
In situ investigations of the effects of mutagenic pollutants (environmental monitoring) have increasingly used bioindicators, and fish often have been used in these studies as sentinel organisms. In the present study, we have used the piscine micronucleus test (MNT) as an in situ biological indicator of chemical contamination in two fresh water fish species (Astyanax bimaculatus and Hoplias malabaricus). The fish were collected in the Japaratuba River (Sergipe, Brazil) in an area impacted by a petrochemical industrial complex (sites 1 and 2) which indirectly contributes treated effluent (produced waters PW) to the river. Responses in fish from these sites were compared to fish from a clean reference site (Jacarecica River - Sergipe, Brazil). The results indicated an enhanced frequency of micronuclei (MN) in peripheral blood erythrocytes of A. bimaculatus collected at site 2 from the Japaratuba River when compared to their respective negative control (A. bimaculatus collected at Jacarecica River). A. bimaculatus collected at site 1 and H. malabaricus collected at sites 1 and 2 from the Japaratuba River did not have a significant increase in MN. The results of this study indicate that the piscine MNT is a useful in vivo technique for the detection of chemical contaminants in the aquatic environment and shows potential for in situ monitoring of water quality. Nevertheless, the results also demonstrated differential sensitivity of A. bimaculatus and H. malabaricus to the induction of MN. The Somatic Mutation and Recombination Test (SMART) of Drosophila melanogaster was applied to assess the genotoxicity of surface (S) and bottom (B) water and sediment samples collected from two sites (Sites 1 and 2) in the Japaratuba River (Sergipe, Brazil), in an area impacted by a petrochemical industrial complex that indirectly discharges treated effluent (produced water - PW) into the river. The genotoxicity tests were based on two samplings taken in March (dry season) and July (rainy season) of 2003. Mutant spot frequencies found in treatments with raw water and sediment samples were compared with frequencies observed in surface water and sediment samples taken from a clean reference site (the Jacarecica River in Sergipe, Brazil) and in negative (ultra pure water) controls. The results indicated that the Jacarecica River cannot be classified as pristine. Hence, for purposes of statistical evaluation, the results were compared with the corresponding negative controls. All the water samples collected in March 2003 were genotoxic. In July 2003, the positive responses were restricted to water samples collected from Sites 1 B and 2 S in the ST cross. The genotoxins found in these samples interacted directly with the DNA of the somatic cells, producing point and/or chromosomal mutation and mitotic recombination. The spot frequencies found in the July samplings were considerably lower than those recorded in March, attesting to the seasonal effect. Sediment proved genotoxic only in samples collected from Site 1 (March and July) and from the Jacarecica River (March). The genotoxins in these samples also acted directly with the DNA, producing somatic mutation and recombination. The findings of this study indicate that the Drosophila wing spot test is an useful in vivo technique for the detection of chemical contaminants in aquatic environments and that this assay is a potential instrument for monitoring water quality.